Development of an autonomous station for measurements of artificial gamma activity in surface water bodies - Fejgl, Michal; Hýža, Miroslav (Journal of environmental radioactivity, 2019)
This paper reports on the structure of the autonomous station for monitoring artificial gamma activity in surface water bodies for the purposes of emergency preparedness of the Czech Republic. A simple design based on the NaI(Tl) submersible detector powered by a combined solar and wind source has been employed. Data transfer is provided by a satellite connection. The detection capabilities of the device have been tested for various unfavourable conditions, and the detection limits have been lowered by using the noise adjustment singular value decomposition (NASVD) method. The detection capabilities of the device fulfil the legal requirements for emergency monitoring, and are almost equal to the detection capabilities of other available devices with a more complicated and less versatile structure.
Keywords: Fresh water monitoring; radioizotopy jodu; Water Pollutants, Radioactive; monitorování radiace; Emergency; radioizotopy cesia; spektrometrie gama; Česká republika; Spectrometry, Gamma; Gamma spectrometry; Gamma Rays; Preparedness; radioaktivní látky znečišťující vodu; Iodine Radioisotopes; Czech Republic; Emergency monitoring; záření gama; (137)Cs; Cesium Radioisotopes; Radiation Monitoring